2021
DOI: 10.2147/opth.s243103
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Ophthalmoscopy: is there a place for it?

Abstract: Smartphone technology is advancing at a rapid pace. Their role in day-to-day life is becoming more and more intricate and irreplaceable. Of late, they have gained immense importance in different medical specialities where they possess an active ability to guide the clinician. This is particularly evident in ophthalmology, where the constantly evolving camera-illumination systems and the artificial intelligence integrated technology have unravelled many novel observations for non-contact posterior segment imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Online teaching can provide flexibility in allowing students to access it from anywhere. If it is a recorded material, they can pause and revisit later [ 8 ]. A systematic review considering learning methods found that ‘blended’ or mixed online and in-person teaching methods showed a consistent benefit when compared to traditional learning [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Online teaching can provide flexibility in allowing students to access it from anywhere. If it is a recorded material, they can pause and revisit later [ 8 ]. A systematic review considering learning methods found that ‘blended’ or mixed online and in-person teaching methods showed a consistent benefit when compared to traditional learning [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, early expert in-hospital ophthalmological examination is an essential component of a comprehensive assessment of patients with UVL. Nonmydriatic ocular fundus photography has been demonstrated to be feasible as an auxiliary tool in the emergency department including the diagnosis of retinal ischemia [ 21 , 22 ], with further technological advances likely to improve usability in various contexts [ 23 ]. Alternatively, innovations in the field of teleophthalmology [ 24 ] may allow for fundus image acquisition in the ambulance, thus enabling expert ophthalmology input at a very early stage of the patient journey.…”
Section: Discussionmentioning
confidence: 99%
“…Another study had also estimated that one out of two physicians incorporates either a smartphone or a personal digital assistant (PDA) in their work and this pattern is expected to increase [16]. However, these devices are yet to be fully applicable as quality diagnostic tools, hence they are limited to screening purposes only as of now [15].…”
Section: Smartphone-based Retinal Imaging Systemmentioning
confidence: 99%
“…Over the years, smartphone-based retinal image acquisition devices have shown its credibility in the medical eld but only up to a certain extent. Despite being affordable, portable, and e cient data transfer with expanding internet technology and arti cial intelligence in smartphones, professionals still nd this method limited to screening purposes only and bene cial only for non-ideal clinical settings [1], [14], [15]. This is because the concept of smartphone-based fundus imaging itself is still incapable of competing against reference standards in terms of image quality and sensitivity.…”
Section: Introductionmentioning
confidence: 99%